2020
DOI: 10.21203/rs.3.rs-23956/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antiviral potential of phytoligands against chymotrypsin-like protease of COVID‐19 virus using molecular docking studies: An optimistic approach

Abstract: A recent outbreak of the novel coronavirus, COVID‐19, in the city of Wuhan, Hubei province, China and its ensuing worldwide spread have resulted in lakhs of infections and thousands of deaths. As of now, there are no registered therapies for treating the contagious COVID‐19 infections, henceforth drug repositioning may provide a fast way out. In the present study, a total of thirty-five compounds including commonly used anti-viral drugs were screened against chymotrypsin-like protease (3CLpro) using SwissDock.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Hence, these 63 phytoligands that prevent or interfere with the ability of SARS-CoV2/3CLpro and SARS-CoV2/PLpro to properly perform their protease functions [4,68] could be chosen as a potential drug for further studies [69]. The anti-protease activity on SARS-CoV1 of most of these compounds has already been reported by other authors [70] including Quercetin and Luteolin on 3CLpro [71,72], Circilineol, Kaempferol, Rhamnetin, and Oleanolic acid on PLpro [73].…”
Section: Discussionmentioning
confidence: 85%
“…Hence, these 63 phytoligands that prevent or interfere with the ability of SARS-CoV2/3CLpro and SARS-CoV2/PLpro to properly perform their protease functions [4,68] could be chosen as a potential drug for further studies [69]. The anti-protease activity on SARS-CoV1 of most of these compounds has already been reported by other authors [70] including Quercetin and Luteolin on 3CLpro [71,72], Circilineol, Kaempferol, Rhamnetin, and Oleanolic acid on PLpro [73].…”
Section: Discussionmentioning
confidence: 85%
“…It has been demonstrated that caffeic acid, as well as the flavone apigenin, could inhibit HCV replication [ 19 , 38 ], while gallic acid, quercetin-3- O -rutinoside (rutin), epigallocatechin-3-gallate (EGCG), and curcumin could inhibit HCV entry [ 25 , 77 , 83 , 101 ]. In hepatitis virus infection, coumarin has been shown to target a wide range of proteins, like binding antigens present at the cell surface, proteins involved in viral replication, and interferon signaling pathways [ 44 ]. Furthermore, it has been demonstrated that sulforaphane, an isothiocyanate widely distributed in Brassicaceae plants, suppresses the replication of HCV by inducing the heme-oxygenase-1 (HO-1) expression, an enzyme that interferes with the replication of the virus through the activation of nuclear factor (erythroid-derived 2)-like (Nrf2) pathway, which regulates the expression of antioxidant proteins [ 124 ].…”
Section: Antiviral Potential Of Selected Natural Phytochemicalsmentioning
confidence: 99%
“…Sahoo et al [ 87 ] used in silico docking approaches to explore the molecular interaction of 13 active compounds extracted from plants against NA protein of H1N1 and observed that theaflavin, found in green tea, could be a potential inhibitor of H1N1 NA proteins, as strongly suggested by lowest docking energy. Molecular docking studies have also shown the inhibitory role against IV infection of coumarin and its derivatives that can target various enzymes and pathways essential for viral entry, survival, and infection [ 44 ]. An in vitro study on the effect of sulforaphane on IAV replication in Madin-Darby canine kidney cells showed a decrease in replication [ 124 ].…”
Section: Antiviral Potential Of Selected Natural Phytochemicalsmentioning
confidence: 99%
“…Plant secondary metabolites like lycorine [6], gingerol shogaol [7], resveratrol rhoifolin [8], oleanolic acid [9], kaempferol [10], rosmarinic acid [11], almond oil [12], ursolic acid [11], hederagenin, nigellidine, and α-hederin [11,13], apigenin, ethyl cholate, nobiletin, tangeretin, chalcone, and hesperidin [10,14,15], epigallocatechin gallate [16], allicin, diallyl trisulfide ajoene, and apigenin [14,17], aloenin [18], artemisinin [6,19], glucobrassicin [10,11], apigenin [11], curcumin [20], piperine [12], flavonoids, anthraquinone, and hydroxychloroquine [21], and jensenone [22] are reported to have antiviral activities. e mechanism of action of these secondary metabolites may be due to their greater binding affinity for SARS-CoV-2 6LU7 and 6Y2E proteases and inhibition of SARS-CoV-2 M protease (Mpro) and Spike (S) glycoprotein [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%